Informal workers’ perceptions of retirement planning in developing countries - Navneel Shalendra Prasad; Amit Prakash; Nikeel Nishkar Kumar (PLoS ONE, 2025)
In this study, we examine the perceptions of informal workers toward retirement planning in developing countries. Specifically, we examine vegetable market vendors’ perceptions of the local superannuation fund, namely the Fiji National Provident Fund (FNPF) in the Western division of Fiji, where agriculture is predominant. The research aims to address the gap in the literature concerning nest egg savings options for the part of the population for whom superannuation contributions are not mandatory. Nest eggs savings are savings and investments for huge financial goals such as retirement. Generally, respondents had a positive outlook on the FNPF, and most responded that they would prefer a tailor-made retirement plan suited to the income and livelihood of market vendors. Specifically, as self-employed people, market vendors are keen for a specialized system of voluntary contributions towards their FNPF accounts that bypasses the mandatory joint-contributions from employers. We also find that age, gender, duration as a market vendor, and other savings avenues are vital for accessibility to financial services offered by the FNPF. We also find that while market vendors are aware of saving and saving benefits with FNPF, there is a lack of intention for them to adopt the current FNPF product. Policymakers must, therefore, develop FNPF products to cater for the needs of market vendors recognizing self-employment and the voluntary nature of contributions.